The relationship between organizational ethical climate factors and job satisfaction - Ting, Ik Leong. (Universiti Malaysia Sarawak, UNIMAS, 2010)
Nowadays, organizations had found out that organizational ethical climate factors are one of the important issues that can lead to increase the employees’ job satisfaction. However, organizations have to be concerned about how to ensure the employees’ job satisfaction at the workplace. This study aimed at exploring the relationship between organizational ethical climate factors (self interest, team interest and laws and professional codes) and job satisfaction. The methodology used in this research was the survey method by using survey research questionnaires as the instrument. Primarily, p ilot test was done by distributing 30 questionnaires randomly to the employees of Hua Seng Sawmill Company Berhad to determine on the validity and reliability of the questionnaires. A total of 103 respondents from the Sibu Municipal Council (SMC) were used as the samples for the actual study in this research. The data from the actual study was also used to undergo pilot test again in order to ensure the validity and reliability of the questionnaires. Besides that, data were analyzed descriptively using freq uencies and percentages. Furthermore, data were also analyzed inferentially by using the Pearson Correlation and Multiple Regression. Pearson Correlation Analysis was used to measure the relationship between the organizational ethical climate factors and j ob satisfaction. All the alternative hypotheses were accepted. The findings and results from the analysis had shown that there was significant relationship between organizational ethical climate factors and job satisfaction. Multiple Regressions was used t o find the dominant factor of organizational ethical climate that affect on job satisfaction. It showed that laws and professional codes was the dominant factor that affect on job satisfaction. In addition, the findings of this research was beneficial for the organizations and future researchers to determine the organizational ethical climate factors that affect on job satisfaction and to identify appropriate method of improving and enhancing job satisfaction at the workplace.